Analisis Bibliometrik Management Risk: Tren Penelitian Keberlanjutan dan Transformasi Digital - Fahmi, Mohamad Ruli; Santoso, Rachmat Agus; Fitriana, Fitriana (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
Research on Risk Management has grown significantly alongside increasing business complexity, digital transformation, and sustainability challenges. This study aims to analyze the development of scientific publications related to Risk Management indexed in the Scopus database using a bibliometric approach through Biblioshiny. The study employed a descriptive quantitative bibliometric method by analyzing 653 scientific articles published 2026. The findings indicate that research on Risk Management has developed rapidly with strong international collaboration. China emerged as the most productive country, while dominant research themes include artificial intelligence, machine learning, sustainability, ESG, and supply chain risk management. Citation analysis also revealed that highly cited articles mainly discuss digital transformation, corporate governance, and technology-based risk management. The study contributes to the development of risk management literature by providing a comprehensive scientific mapping and identifying future research opportunities in digital and sustainability-based risk management.